Large deflection analysis of a fiber reinforced composite beam - Akbaş, Şeref Doğuşcan (Techno-Press, 2018)
The objective of this work is to analyze large deflections of a fiber reinforced composite cantilever beam under point loads. In the solution of the problem, finite element method is used in conjunction with two dimensional (2-D) continuum model. It is known that large deflection problems are geometrically nonlinear problems. The considered non-linear problem is solved considering the total Lagrangian approach with Newton-Raphson iteration method. In the numerical results, the effects of the volume fraction and orientation angles of the fibre on the large deflections of the composite beam are examined and discussed. Also, the difference between the geometrically linear and nonlinear analysis of fiber reinforced composite beam is investigated in detail.
Akbas, Seref Doguscan/0000-0001-5327-3406
Keywords: large deflection analysis; fiber reinforced composite beam; total Lagragian; Finite Element Method